Pesticides Exposure and Thyroid Hormone Levels Among Agricultural Workers and Pesticide Applicators: A Systematic Review - Suratman Suratman; Suhartono Suhartono (JURNAL KESEHATAN LINGKUNGAN, 2022)
Introduction: Presently, the global consumption of pesticides including insecticides, herbicides, and fungicides to protect crops is increasing. Pesticides' role as Endocrine-Disrupting Chemicals (EDCs) has gained great concern in the field of thyroid hormones. Therefore, this systematic review aimed to determine the link of pesticide exposure with thyroid hormone levels among male agricultural workers and pesticide applicators. Discussion: It was discovered that the majority of reviewed articles have similar results concerning the effects of pesticide exposure on the serum levels of thyroid hormones among either farmworkers or pesticide applicators. Commonly, insecticides, herbicides, and fungicides are known as one of the EDCs. The results showed the elevation of TSH and T4 serum levels mostly occurred among groups exposed to insecticide application only rather than those exposed to various pesticide types. Moreover, the hormonal change differed based on each class of pesticide. Conclusion: This review suggests that some types of pesticides extensively used in agriculture might be involved in the increase and decrease in thyroid hormone levels among exposed individuals. Further studies should assess specific types of pesticides and the adverse health effects which involve confounding factors to yield robust analysis.